EDUCATIONAL NEUROSCIENCE AND DIGITAL TECHNOLOGIES IN INTERACTION WITH DAILY SCHOOL LIFE - Pereira Nicácio, Jailton; Trajano de Souza, Joseilson; Trajano de Souza, Josenete; Lisboa Galvão do Nascimento, Jonatha; Modesto Favacho, Kelsin; Helena de Paula Modesto Favacho, Lucia; Santos do Nascimento, Marielza; Campos Rodrigues, Mayara; Ricardo Pereira Accioly, Sérgio (Revista Gênero e Interdisciplinaridade, 2026)
In school spaces permeated by digital devices, the effects are not limited to the visible practice of teaching — there are more subtle shifts that affect the way learning is perceived, felt, and organized. The contributions of neuroscience, by illuminating the processes of synaptic activation and emotional response to multimodal stimuli, indicate that learning occurs in a network, not in a straight line. Each gesture of attention or distraction calls upon the entire body, the entire context, and the entire language, requiring the educator to listen in an expanded, situated, and sensitive way. In this context, the presence of technology does not represent an obstacle to concentration but demands new forms of mediation and listening. Teachers who understand the neural processes involved in learning can create strategies that are more sensitive to the contemporary rhythms of attention, memory, and meaning. Digital technology, when used as a formative territory and not as a distraction, allows the school experience to be reorganized in tune with current modes of producing meaning. The research proposal that supports this study is based on the interest in understanding how educational practices can be reconstructed considering the knowledge produced by neuroscience, especially when placed in dialogue with the daily use of digital resources. A qualitative methodological approach was chosen, structured based on critical bibliographic research, mobilizing authors who deal with the relationships between cognitive processing, synaptic reorganization, emotional language and formative experiences mediated by technological devices.